Consumers’ preferences on usefulness and consumption of enriched products - Kralik, Zlata (Array, 2018)
The aim of this study was to assess the preferences of consumers on usefulness and consumption of enriched and/or functional food products with a focus on table eggs. The survey of consumers' preferences on usefulness and consumption of enriched as well as functional products was conducted on a sample of 132 respondents. Data were collected using a questionnaire survey consisting of 15 questions. The first 7 questions related to socio-demographic characteristics of the respondents (gender, age, education, marital status, occupation, income, etc.). The second part of the questionnaire consisted of 8 questions related to obtaining information on the will to purchase the aforementioned products, the health benefits of functional ingredients in enriched products, validity or scientific confirmation of declarations and the like. More women (60.6%) than men (39.4%) participated in the survey. Overall, the survey was completed by mostly young people, aged 19-29 (53%), highly educated (68.94%) with earnings of over 5001 kn (60.6%). According to respondents’ opinion on the usefulness and correctness of enriched or functional products as well as the willingness to consume omega-3 eggs, most of them did not really have any opinion on these products, which is confirmed with the fact that highest frequency of answers to the asked questions was 4. Considering that the majority of respondents were of a younger age and according to the fact that they did not have defined opinion on enriched products, it is necessary to educate on the importance of these products in the diet.